Authoritarian experience and electoral success: the fate of authoritarian diasporans in Kenya. Issue 3 (3rd April 2021) - LeBas, Adrienne; Gray, Kyle
ABSTRACT: Since the early 1990s, many African countries have instituted multiparty elections and experienced electoral turnover. Despite this apparent change, politics in many places remains dominated by politicians who defected from the former authoritarian ruling party and won power on rival party tickets. Kenya is seen as a paradigmatic case of this kind of authoritarian "diaspora". After the defeat of the Kenya African National Union (KANU) in 2002, the party entered into fairly speedy decline, yet the country has yet to elect a president or deputy president who did not previously hold office in KANU. Former KANU office-holders also composed significant proportions of cabinet appointees after KANU's defeat in 2002. But how far down the ladder of political office does the prevalence of "diasporans" extend? In the first multiparty elections of 1992, 1997, and 2002, we show that KANU diasporans compose a sizeable proportion of candidates in parliamentary elections, and both "strong" and "weak" diasporans were more successful in winning election than new political entrants. This suggests that, overall, Kenyan voters do not consistently sanction diasporans for their authoritarian pasts. These findings have implications for our understanding of democratization and party development in hybrid regimes.